FANDOM


Let me publish some comparisons which show that actual limit of sub-legion BEAF is \theta(\Omega^\Omega).

From \(\varepsilon_0\) to \(\Gamma_0\)

\{\omega,\omega,2\} = \varepsilon_0

\{\omega,\omega+1,2\} = {\varepsilon_0}^{\varepsilon_0}

\{\omega,\omega+2,2\} = {\varepsilon_0}^{{\varepsilon_0}^{\varepsilon_0}}

\{\omega,\omega+m,2\} = \varepsilon_0 \uparrow\uparrow (m+1)

\{\omega,\omega*2,2\} = \varepsilon_1

\{\omega,\omega*2+m,2\} = \varepsilon_1 \uparrow\uparrow (m+1)

\{\omega,\omega*3,2\} = \varepsilon_2

\{\omega,\omega*(1+\alpha),2\} = \varepsilon_\alpha

\{\omega,\omega^2,2\} = \varepsilon_\omega

\{\omega,\omega^\omega,2\} = \varepsilon_{\omega^\omega}

\{\omega,\{\omega,\omega,2\},2\} = \varepsilon_{\varepsilon_0}

\{\omega,\omega,3\} = \zeta_0

\{\{\omega,\omega,3\},\omega,2\} = \varepsilon_{\zeta_0+1}

\{\omega,\omega+1,3\} = \varepsilon_{\zeta_0*2}

\{\omega,\omega+2,3\} = \varepsilon_{\varepsilon_{\zeta_0*2}}

\{\omega,\omega*2,3\} = \zeta_1

\{\omega,\omega*(1+\alpha),3\} = \zeta_\alpha

\{\omega,\omega^\omega,3\} = \zeta_{\omega^\omega}

\{\omega,\{\omega,\omega,3\},3\} = \zeta_{\zeta_0}

\{\omega,\omega,4\} = \eta_0

\{\{\omega,\omega,4\},\omega,2\} = \varepsilon_{\eta_0+1}

\{\{\omega,\omega,4\},\omega,3\} = \zeta_{\eta_0+1}

\{\omega,\omega+1,4\} = \zeta_{\eta_0*2}

\{\omega,\omega+2,4\} = \zeta_{\zeta_{\eta_0*2}}

\{\omega,\omega*2,4\} = \eta_1

\{\omega,\omega*(1+\alpha),4\} = \eta_\alpha

\{\omega,\{\omega,\omega,4\},4\} = \eta_{\eta_0}

\{\omega,\omega,5\} = \theta(4,0)

\{\omega,\omega*(1+\alpha),1+m\} = \theta(m,\alpha)

\{\omega,\omega,\omega\} = \theta(\omega,0)

\{\{\omega,\omega,\omega\},2,2\} = \theta(\omega,0)^{\theta(\omega,0)}

\{\{\omega,\omega,\omega\},2,3\} = \epsilon_{\theta(\omega,0)*2)}

\{\{\omega,\omega,\omega\},2,4\} = \zeta_{\theta(\omega,0)*2)}

\{\{\omega,\omega,\omega\},2,5\} = \eta_{\theta(\omega,0)*2)}

\{\omega,\omega+1,\omega\} = \theta(\omega,1)

\{\omega,\omega+m,\omega\} = \{\{\omega,\omega,\omega\},m+1,\omega\} = \theta(\omega,1)

\{\omega,\omega*2,\omega\} = \theta(\omega,1)

\{\omega,\omega*(1+\alpha),\omega\} = \theta(\omega,\alpha)

\{\omega,\omega,\omega+1\} = \theta(\omega+1,0)

\{\{\omega,\omega,\omega+1\},2,\omega\} = \theta(\omega,\theta(\omega+1,0)+1)

\{\omega,\omega+1,\omega+1\} = \theta(\omega,\theta(\omega+1,0)*2)

\{\omega,\omega*2,\omega+1\} = \theta(\omega+1,1)

\{\omega,\omega*(1+\alpha),\omega+1\} = \theta(\omega+1,\alpha)

\{\omega,\omega*(1+\alpha),1+\beta\} = \theta(\beta,\alpha)

\{\omega,\omega,\{\omega,\omega,\omega\}\} = \theta(\theta(\omega,0),0)

\{\omega,\omega,1,2\} = \theta(\Omega,0)

Above \(\Gamma_0\)

\{\omega,\omega+1,1,2\} = \{\{\omega,\omega,1,2\},\{\omega,\omega,1,2\},\{\omega,\omega,1,2\}\} = \theta(\theta(\Omega,0),\theta(\Omega,0)).

\{\omega,\omega*2,1,2\} = \theta(\Omega,1)

\{\omega,\omega*(1+\alpha),1,2\} = \theta(\Omega,\alpha)

\{\omega,\omega,2,2\} = \theta(\Omega+1,1)

\{\omega,\omega*(1+\alpha),1+\beta,2\} = \theta(\Omega+\beta,\alpha)

\{\omega,\omega,\{\omega,\omega,1,2\},2\} = \theta(\Omega+\theta(\Omega,0),0)

\{\omega,\omega,1,3\} = \theta(\Omega*2,0)

\{\omega,\omega*(1+\alpha),1+\beta,1+\lambda\} = \theta(\Omega*\lambda+\beta,\alpha)

\{\omega,\omega,1,1,2\} = \theta(\Omega^2,0)

\{\omega,\omega*(1+\alpha_0),1+\alpha_1,1+\alpha_2,1+\alpha_3\} = \theta(\Omega^2*\alpha_3+\Omega*\alpha_2+\alpha_1,\alpha_0)

\{\omega,\omega,1,1,1,2\} = \theta(\Omega^3,0)

\{\omega,\omega*(1+\alpha_0),1+\alpha_1,\cdots,1+\alpha_m\} = \theta(\Omega^{m-1}*\alpha_m+\cdots+\Omega*\alpha_1,\alpha_0)

\{\omega,\omega,1,\cdots,1,2\} = \theta(\Omega^m)

\{\omega,\omega (1) 2\} = \theta(\Omega^\omega)

\{\omega,\omega+1 (1) 2\} = \theta(\Omega^\omega)^{\theta(\Omega^\omega)}

\{\omega,\omega+2 (1) 2\} = \theta(\theta(\Omega^\omega),\theta(\Omega^\omega))

\{\omega,\omega+3 (1) 2\} = \theta(\Omega*\theta(\Omega^\omega)+\theta(\Omega^\omega),\theta(\Omega^\omega))

\{\omega,\omega*2 (1) 2\} = \theta(\Omega^\omega,1)

\{\omega,\omega*(1+\alpha) (1) 2\} = \theta(\Omega^\omega,\alpha)

\{\omega,\omega,2 (1) 2\} = \theta(\Omega^\omega+1,0)

\{\omega,\omega*(1+\alpha),1+\beta (1) 2\} = \theta(\Omega^\omega+\beta,\alpha (1) 2\}

\{\omega,\omega,1,2 (1) 2\} = \theta(\Omega^\omega+\Omega,0)

\{\omega,\omega*(1+\alpha),1+\beta,1+\lambda (1) 2\} = \theta(\Omega^\omega+\Omega*\lambda+\beta,\alpha)

\{\omega,\omega,1,1,2 (1) 2\} = \theta(\Omega^\omega+\Omega^2,0)

\{\omega,\omega,1,\cdots,1,2 (1) 2\} = \theta(\Omega^\omega+\Omega^m,0)

\{\omega,\omega (1) 3\} = \theta(\Omega^\omega*2,0)

\{\omega,\omega,2 (1) 3\} = \theta(\Omega^\omega*2+1,0)

\{\omega,\omega,1,\cdots,1,2 (1) 3\} = \theta(\Omega^\omega*2+\Omega^m,0)

\{\omega,\omega (1) 4\} = \theta(\Omega^\omega*3,0)

\{\omega,\omega (1) 1+\alpha\} = \theta(\Omega^\omega*\alpha,0)

\{\omega,\omega (1) 1,2\} = \theta(\Omega^{\omega+1},0)

\{\omega,\omega (1) 1+\alpha,2\} = \theta(\Omega^{\omega+1}+\Omega^\omega*\alpha,0)

\{\omega,\omega (1) 1,3\} = \theta(\Omega^{\omega+1}*2,0)

\{\omega,\omega (1) 1+\beta,1+\alpha\} = \theta(\Omega^{\omega+1}*\alpha+\Omega^\omega*2,0)

\{\omega,\omega (1) 1,1,2\} = \theta(\Omega^{\omega+2},0)

\{\omega,\omega (1) 1,\cdots,1,2\} = \theta(\Omega^{\omega+m},0)

\{\omega,\omega (1)(1) 2\} = \theta(\Omega^{\omega*2},0)

\{\omega,\omega,1,\cdots,1,2 (1)(1) 2\} = \theta(\Omega^{\omega*2}+\Omega

\{\omega,\omega (1) 2 (1) 2\} = \theta(\Omega^{\omega*2}+\Omega^{\omega},0)

\{\omega,\omega (1) 1,\cdots,2 (1) 2\} = \theta(\Omega^{\omega*2}+\Omega^{\omega+m},0)

\{\omega,\omega (1)(1) 3\} = \theta(\Omega^{\omega*2}*2,0)

\{\omega,\omega (1)(1) 1+\alpha\} = \theta(\Omega^{\omega*2}*\alpha,0)

\{\omega,\omega (1)(1) 1,\cdots,2\} = \theta(\Omega^{\omega*2+m},0)

\{\omega,\omega (1)(1)(1) 2\} = \theta(\Omega^{\omega*3},0)

\{\omega,\omega (2) 2\} = \theta(\Omega^{\omega^2},0)

\{\omega,\omega (\alpha) 2\} = \theta(\Omega^{\omega^\alpha},0)

&(\omega,\omega,\alpha) = \theta(\Omega^\alpha,0)

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.